Infection of Helicobacter pylori and Atrophic Gastritis Influence Lactobacillus in Gut Microbiota in a Japanese Population - Iino, Chikara; Shimoyama, Tadashi; Chinda, Daisuke; Arai, Tetsu; Chiba, Daisuke; Nakaji, Shigeyuki; Fukuda, Shinsaku (Frontiers in Immunology, 2018)
Background: Suppression of gastric acid by proton pump inhibitors (PPIs) is associated with the increase of Lactobacillus in human gut microbiota. Gastric acid secretion is also suppressed by Helicobacter pylori infection and following atrophic gastritis. However, few studies have examined the association between H. pylori infection and Lactobacillus species in gut microbiota particularly in Japan. Methods: A total of 1123 adult subjects who participated in a health survey in Hirosaki City were studied. Infection of H. pylori was defined by both serum antibody and stool antigen test. The presence and the severity of atrophic gastritis were defined by the serum level of serum pepsinogens. Using 16S ribosomal RNA amplification from fecal samples, the relative abundance of Lactobacillus was calculated and the composition ratio of each Lactobacillus species were surveyed. Results: The relative abundance of the Lactobacillus in H. pylori infected subjects with severe atrophic gastritis was higher comparing with those in subjects with mild atrophic gastritis and without atrophic gastritis (0.591% vs 0.068% and 0.033%, respectively; p<0.001) and also that of non-infected subjects (0.033%; p<0.001). In H. pylori non-infected subjects, both gender and age were not associated with the relative abundance of Lactobacillus in fecal samples. The proportion of L. salivarius was high in H. pylori infected subjects while that of L. acidophilus was high in non-infected subjects. Conclusion: Lactobacillus in human gut microbiota could be influenced by H. pylori infection and severity of atrophic gastritis in Japanese subjects.